Aesthetics of Food Porn - Uku Tooming (Crítica)
Enticing food photography which stimulates its viewers’ cravings, often given a dismissive label “food porn,” is one of the most popular contents in contemporary digital media. In this paper, I argue that the label disguises different ways in which a viewer can engage with it. In particular, food porn enables us to engage in cross-modal gustatory imaginings of a specific kind and an image’s capacity to afford such imaginings can contribute to its artistic merit.